COMPARISONAL ANALYSIS OF BANKING FINANCIAL PERFORMANCE BEFORE AND AFTER ADOPTING IFRS - Achmad Daengs GS; Enny Istanti; Diana Zuhro; Retno Susanti; Ruhan Sanusi; Sutini Sutini; Bramastyo Kusumonegor (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to analyze the comparison of financial performance of banks before and after the adoption of International Financial Reporting Standards (IFRS) in Indonesia. The type of data used is secondary data taken from the balance sheets of banks listed on the Indonesia Stock Exchange (IDX) for the period 2010-2013. The variables used are financial ratios with Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) indicators. This study uses quantitative methods, data were analyzed with a paired t-test. The results show that the implementation of IFRS has no impact on the financial performance of banks, because in principle the implementation of IFRS is not directly aimed at improving performance.